KEDUDUKAN AHLI WARIS PENGGANTI DALAM KOMPILASI HUKUM ISLAM - Barhamudin, Barhamudin (Solusi, 2017)
ABSTRACT The purpose of the research is to know the extent of replacement place of heirs in the compilation of Islamic law. Legal research is a scientific activity based on certain methods, systems, and thoughts that aim to study one or all of the laws by analyzing them and this type of research is a normative legal research. (normative juridical), namely leg al research conducted by prioritizing research library or documents called secondary data, in the form of primary, secondary, and tertiary legal materials. The materials obtained from the research that is done secondary data, to the data is done as follows: Selecting the articles and verses and opinions of the jurists who contains the legal precepts that regulate the problem of replacement heirs. The results obtained that the Islamic inheritance law determines, the child can replace his father's position is the son and daughter of the male lineage whose father had died first from the heir, while the boys and girls of the female lineage is not entitled entirely to replace his mother's position to obtain property from his grandfather (heir). The grandson of a new boy can replace his parent's position if the heir does not leave the other surviving son. And the right of the surrendered heir is not necessarily the same as the right of the person to be replaced, nor should it be exceeded from the part of the heirs who are equal to the substituted, but may be reduced. Likewise, based on Article 185 of the Compilation of Islamic Law, grandchild may be the surrogate heir and replace the position of his parents. Grandchildren will have an inheritance equal to the share earned by his parents if he were alive. The surrogate heirs aims to safeguard the right of the beneficiary who should receive the part of the heiress who is passed on to his successor ie his son for continued family survival also strengthens the brotherhood between the heirs and the successor heirs.